AB0741 Non Response to TNF-Inhibitor Therapy in Ankylosing Spondylitis is Associated with Restricted Spinal Mobility. (9th June 2015) - Sari, I.; Inman, R.D.; Chan, J.; Omar, A.; Ayearst, R.; Haroon, N.
Abstract : Background: TNF-inhibitor biological agents represent a significant advance in the treatment of spondyloarthritis (SpA). Despite their effectiveness some patients require a change in treatment because of lack of efficacy or adverse reactions. In the current literature, there are a limited number of studies addressing the predictors of switching in patients with axial SpA. Objectives: The aim of this study was to investigate the associated factors of anti-TNF switching in patients with ankylosing spondylitis (AS) and non-radiographic axial SpA (nr-ax-SpA). Methods: Patients with a diagnosis of AS or nr-ax-SpA, who previously failed at least one anti-TNF treatment for lack of efficacy were included in the study. Other forms of SpA (psoriatic arthritis, reactive arthritis and enteropathic arthritis) were excluded. In addition to disease activity and acute phase measures; HLA-B27 status, history uveitis, history of arthralgia/arthritis, smoking status and family history of AS were collected on all patients in whom baseline data (BASFI, BASDAI, BASMI, ESR and CRP) was available. Notation was made of the modified Stoke AS Spine Score (mSASSS) and radiographic hip involvement for each patient. Correlation analysis and logistic regression were performed to evaluate the factors predictive of switching. Results: There were 183 AxSpA patients (81.4% AS, 18.6% nr-axSpA) in the study. 53 (38.1%) out of 183 patients had at least one switch due to lack of efficacy. Comparison of switchers with patients who did not change biologics revealed that age, sex, diagnostic category, disease duration, BASFI, BASDAI, ESR, CRP, HLA-B27 status, frequency of hip involvement and family history of SpA were not different between the groups ( p >0.05, Table-1 ). BASMI was significantly higher in the group of switchers ( p =0.03; 3.6±2.4 vs. 2.6±2.2). In logistic regression, among the variables included in the model (total mSASSS, hip involvement, HLAB-27 status, baseline values of BASFI, BASDAI, BASMI, CRP and ESR), only baseline BASMI predicted the anti-TNF change ( p =0.04, β=1.48 [95% CI=1.01-2.17]). Conclusions: This is the first study to suggest that limitation in spinal mobility, is associated with lower response to TNFi therapy. In contrast, baseline indicators of disease activity did not predict response to TNFi. There were no differences observed in nr-axSpA in comparison with AS, further emphasizing commonalities between these clinical subsets. Disclosure of Interest: None declared